Implementation of the Culturally Responsive Teaching Approach to Increase Student Learning Motivation in Pancasila Education Subjects at SD Plus IGM, Palembang City - Annisa Maharani; Yenny Anwar; Atika Dwi Maryanti (UIN Fatmawati Sukarno Bengkulu, 2025)
The implementation of the Culturally Responsive Teaching (CRT) approach aims to enhance student motivation in the Pancasila Education subject for Grade V students at SD Plus Indo Global Mandiri (IGM) in Palembang. This study was motivated by the issue of low learning motivation among students in the Pancasila Education subject, as observed during the initial teaching practicum (PPL 1). The preliminary observation revealed that only 49.96% of students demonstrated sufficient learning motivation. This condition was primarily caused by the use of teacher-centered learning approaches that relied heavily on textbooks, lacked variety, and failed to connect the material to students' cultural backgrounds and real-life experiences. The purpose of this study was to increase students’ learning motivation through the application of Culturally Responsive Teaching (CRT), a teaching approach that integrates students’ cultural backgrounds as a foundation to build deeper understanding of the subject matter. This research employed a Classroom Action Research (CAR) design, which was conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The subjects of this study were Grade V students at SD Plus IGM Palembang. Data on student motivation were collected using a motivation questionnaire administered during each cycle. The data were analyzed quantitatively by calculating the percentage of improvement in students’ learning motivation. The findings showed a significant increase in students’ motivation after the implementation of the CRT approach. Learning motivation rose from 49.96% in the pre-cycle to 73.24% in the first cycle, and further increased to 88.16% in the second cycle. This improvement indicates that the CRT approach can foster a more relevant, engaging, and enjoyable learning experience, which positively impacts students’ motivation in learning Pancasila Education.